ПІДВИЩЕННЯ ЕФЕКТИВНОСТІ ВИКОРИСТАННЯ АВТОТРАНСФОРМАТОРА ЗІ СТРИЖНЕВИМ МАГНІТОПРОВОДОМ У СКЛАДІ ТРАНСФОРМАТОРНО-КЛЮЧОВОЇ ВИКОНАВЧОЇ СТРУКТУРИ СТАБІЛІЗАТОРА НАПРУГИ ЗМІННОГО СТРУМУ - Липківський, К.О.; Можаровський, А.Г. (Інститут електродинаміки Національної академії наук України, 2020)
The autotransformer (AT) of the transformer-and-switches executive structure (TSES) of an AC voltage stabilizer largely determines the overral dimensions of the converter. One of the methods to increase the efficiency of using the installed power of the AT is the targeted redistribution of losses in the elements of the AT, which can reduce the unevenness of their heating, increase the current density in its windings and, as a result, increase the load current and its allowable power. The paper traces the features of this procedure and its consequences for a TSES with an autotransformer which has a core magnetic circuit, the possible choice of which is one of a number of manifestations of the multivariance of the construction of a transformer-and-switches executive structure. References 12, figures 2, table.